Echinocandins Compared to Fluconazole for Candidemia of a Urinary Tract Source: A Propensity Score Analysis. (3rd February 2017) - Cuervo, Guillermo; Garcia-Vidal, Carolina; Puig-Asensio, Mireia; Vena, Antonio; Meije, Yolanda; Fernández-Ruiz, Mario; González-Barberá, Eva; Blanco-Vidal, María José; Manzur, Adriana; Cardozo, Celia; Gudiol, Carlota; Montejo, José Miguel; et al.
Summary: Echinocandin therapy was not associated with clinical failure when used for patients with ascending urinary source candidemia. Acute renal failure was a predictor of worse outcomes, whereas performing an early urologic procedure was a protective measure. Abstract: Background: Whether echinocandins could be used to treat candidemia of a urinary tract source (CUTS) is unknown. We aimed to provide current epidemiological information of CUTS and to compare echinocandin to fluconazole treatment on CUTS outcomes. Methods: A multicenter study of adult patients with candidemia was conducted in 9 hospitals. CUTS was defined as a candidemia with concomitant candiduria by the same organism associated with significant urological comorbidity. The primary outcome assessed was clinical failure (defined by 7-day mortality or persistent candidemia) in patients treated with either an echinocandin or fluconazole. A propensity score was calculated and then entered into a regression model. Results: Of 2176 episodes of candidemia, 128 were CUTS (5.88%). Most CUTS cases were caused by Candida albicans (52.7%), followed by Candida glabrata (25.6%) and Candida tropicalis (16.3%). Clinical failure occurred in 7 patients (20%) treated with an echinocandin and in 15 (17.1%) treated with fluconazole ( P = .730). Acute renal failure (adjusted odds ratio [AOR], 3.01; 95% confidence interval [CI], 1.01–8.91; P = .047) was the only independent factor associated with clinical failure, whereas early urinary tract drainage procedures (surgical, percutaneous, or endoscopic) were identified as protective (AOR, 0.08; 95% CI, .02–.31; P < .001). Neither univariate nor multivariate analysis showed that echinocandin therapy altered the risk of clinical failure. Conclusions: Initial echinocandin therapy was not associated with clinical failure in patients with CUTS. Notably, acute renal failure predicted worse outcomes and performing an early urologic procedure was a protective measure.